ANALYSIS OF THE INFLUENCE OF THE EXPOSURE CAREER FUNCTION OF MENTORSHIP ON WOMEN’S LEADERSHIP ADVANCEMENT IN KENYAN UNIVERSITIES - Severina, Wambeti Njagi; Edabu, Dr. Paul; Kimani, Dr. Cecilia (IJRDO- Journal of Educational Research, 2016)
Women working in Kenyan universities should be provided with the many benefits of exposure which is a mentorship function. They shoukd for example get support in networking. This however may not be taking place in these universities. Therefore, the researcher did this study for the purpose of determining the influence of exposure on women’s leadership advancement in Kenyan universities. A mixed methodology, using a triangulation design-convergence model was applied to realize the objective. The findings were that the women have limited exposure, thus their chances of leadership advancement are hindered. The conclusion was that women working in Kenyan universities should get enough exposure so that their chances of leadership advancement can be enhanced. Data analysis for example demonstrated that in Kenyan universities, mentors rarely give mentees opportunities to demonstrate their knowledge and network extensively. Women in universities should be fully exposed so as to meet important people who can help them advance.